The Development of Social Preparedness of Sport Pedagogues in the Context of Social Training - Malinauskas, Romualdas (Acta Paedagogica Vilnensia, 2003)
The paper seeks to reveal the development of social preparedness of sport pedagogues in the context of social training. The work outlines the dependency of students’ (future sport pedagogues’) social preparedness upon pedagogic practice as one of the most important forms of social training. The research problem originates from the lack of data on what is the role of social training (in our case – pedagogic practice) in the development of social preparedness of future sport pedagogues in the context of social training. The goal of the research is to reveal the development of social preparedness of spurt pedagogues in the context of social training. The object of the research is the development of social preparedness before and after social training. Research tasks: 1) to establish by the method of questioning whether the level of components (social competence, aiming for status, and disposition for escaping failures) of sport pedagogues’ social preparedness is different before and after social training; 2) by the method of observation to compare the level of sport pedagogues' social preparedness before and after social training. The investigation was organised in two stages. In 2000, 139 future sport pedagogues of the Faculty of pedagogy, Lithuanian Academy of Physical Education, were tested. In 2001, the same investigation was repeated. The investigation was provided with the same 139 students. It was defined that after the pedagogic practice students (future sport pedagogues) were statistically reliably more competent socially. Statistically reliable differences were revealed regarding the capability of sport pedagogues to create emotionally positive and business-like relations connected to the problem solution: during the second pedagogic practice future sport pedagogues were striving more for solidarity, communicating more easily, approving more often, proposing more frequently, indicating the direction of activity, expressing personal opinion and explaining more frequently.
Keywords: higher education; teacher education; social preparedness; sport pedagogues; social training